Formulation, Standardization and Nutritional Analysis of Beverage and Chutney recipes using Cassia auriculata - Thirumalaiselvi , K; Sugumar, Raji V (International Journal of Scientific Research in Biological Sciences, 2024)
In this study, the effects of Cassia auriculata, a herb, on the formation, standardization, and nutritional analysis (Macro and Micro nutrients) of beverage and chutney recipes were investigated. The flowers, buds, and leaves of the herb exhibited the highest antioxidant activity due to their elevated phenolic and flavonoids content. The aqueous shade-dried powder from the leaves, flowers, and buds was used in the preparation of the beverage mix and chutney mix, which were formulated and standardized using natural preservatives. The edible flowers, buds, and leaves were found to be non-toxic and innocuous, with potential health benefits when consumed in the human diet. The prepared beverage mix and chutney mix were subjected to nutritional analysis, and the organoleptic evaluation by a panel of semi-trained participants showed encouraging acceptability for up to 120 days of storage at room temperature. This study demonstrates the feasibility of utilizing Cassia auriculata as a natural ingredient in the development of shelf-stable and nutritionally-rich beverage and chutney mixes, without the addition of artificial preservatives or flavours. This diversity in formulations also opens avenues for innovative culinary applications and commercial product development, potentially expanding the plant`s consumption. Incorporating this ethno medicinal herb into your regular diet, either as a drink or in a recipe, may help to revitalize your body`s overall system.